2010
DOI: 10.1084/jem.20100797
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 facilitates somatic cell reprogramming and augments the malignant potential of reprogrammed cells

Abstract: p53 deficiency enhances the efficiency of somatic cell reprogramming to a pluripotent state. As p53 is usually mutated in human tumors and many mutated forms of p53 gain novel activities, we studied the influence of mutant p53 (mut-p53) on somatic cell reprogramming. Our data indicate a novel gain of function (GOF) property for mut-p53, which markedly enhanced the efficiency of the reprogramming process compared with p53 deficiency. Importantly, this novel activity of mut-p53 induced alterations in the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 56 publications
7
117
0
Order By: Relevance
“…Mutant p53 also is found to promote invasion, loss of directionality of migration, and metastatic behavior via increased recycling of integrin (11). In addition, mutant p53 is found to facilitate somatic cell reprogramming and augments the malignant potential of reprogrammed cells (12). A recent study showed that mutant p53 can compete with wild-type p53 to promote epithelial-to-mesenchymal transition (EMT) 2 and regulate the EMT-associated stem cell-like phenotype (13).…”
mentioning
confidence: 99%
“…Mutant p53 also is found to promote invasion, loss of directionality of migration, and metastatic behavior via increased recycling of integrin (11). In addition, mutant p53 is found to facilitate somatic cell reprogramming and augments the malignant potential of reprogrammed cells (12). A recent study showed that mutant p53 can compete with wild-type p53 to promote epithelial-to-mesenchymal transition (EMT) 2 and regulate the EMT-associated stem cell-like phenotype (13).…”
mentioning
confidence: 99%
“…9 Furthermore, mutp53 strongly enhances reprogramming efficiency and can replace one of the classical reprogramming factors, but the resulting cells are highly tumorigenic. 57 The "epigenetic alteration of transcription" by mutp53 would very likely be intrinsically stochastic due to slight differences in the transcriptional status of single cells. In fact, the observed variability in the gene expression pattern observed upon mutp53 depletion supports such a stochastic model for gene regulation by mutp53.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These and subsequent studies demonstrated that virtually all cell types can generate induced pluripotent stem (iPS) cells when the appropriate reprogramming gene sets are used, which supports the hypothesis that most, if not all, somatic mammalian cells possess dedifferentiation potential and confirms the inherent reversibility of the steps of cellular differentiation. The fact that several reprogramming transcription factors represent bona fide oncogenes, whereas many genes that act as barriers to nuclear reprogramming correspond to known tumor suppressors (e.g., p53), [45][46][47][48][49][50] strongly suggests that the necessary epigenetic rewiring for cellular reprogramming may be partially recapitulated during cellular transformation. Accordingly, the use of an iPS cell expression signature comprised of genes that are consistently upregulated in independent studies with iPS cultures has revealed significant similarities between p53-mutated cancers and cells that have undergone intentional reprogramming in vivo.…”
Section: Precog-ips Cells and Precrime-mouse Avatarsmentioning
confidence: 99%